New evolutionary sequences for the hot H-deficient white dwarfs on the basis of a full account of progenitor evolution - Althaus, Leandro Gabriel (2009)
We present full evolutionary calculations appropriate for the study of hot hydrogen-deficient DO white dwarfs, PG 1159 stars, and DB white dwarfs. White dwarf sequences are computed for a wide range of stellar masses and helium envelopes on the basis of a complete treatment of the evolutionary history of progenitors stars, including the core hydrogen and helium burning phases, the thermally pulsing asymptotic giant branch phase, and the born-again episode that is responsible for the hydrogen deficiency. We also provide colors and magnitudes for the new sequences for Teff < 40,000 K, where the NLTE effects are not dominant. These new calculations provide a homogeneous set of evolutionary tracks appropriate for mass and age determinations for both PG 1159 stars and DO white dwarfs. The calculations are extended down to an effective temperature of 7000 K. We applied these new tracks to redetermine stellar masses and ages of all known DO white dwarfs with spectroscopically determined effective temperatures and gravities, and compare them with previous results. We also compare for the first time consistent mass determinations for both DO and PG 1159 stars, and find a considerably higher mean mass for the DO white dwarfs. We discuss as well the chemical profile expected in the envelope of variable DB white dwarfs from the consideration of the evolutionary history of progenitor stars. Finally, we present tentative evidence for a different evolutionary channel, other than that involving the PG 1159 stars, for the formation of hot, hydrogen-deficient white dwarfs